Prevalence of Allergic Rhinitis based on World Health Organization (ARIA-WHO) questionnaire among Batch 2010 Students of the Faculty of Medicine Universitas Padjadjaran - Fauzi, Fauzi; Sudiro, Melati; Lestari, Bony Wiem (Althea Medical Journal, 2015)
Background: Allergic rhinitis (AR) is a common disease affecting 5â45% of Asian population. Although itÂ is not a life-threatening disease, AR significantly hampers the quality of life of the sufferers. The prevalenceÂ of AR among adults in Indonesia is still unknown. This study aimed to measure the prevalence of AR amongÂ batch 2010 students of the Faculty of Medicine, Universitas Padjadjaran.Methods: A cross-sectional study was conducted during JuneâOctober 2013 involving Indonesian classÂ batch 2010 students of the Faculty of Medicine, Universitas Padjadjaran. The sampling was performed usingtotal sampling approach. The measurement tool used in this study was the Indonesian translation of theÂ Allergic Rhinitis and its Impact on Asthma-World Health Organization (ARIA-WHO) questionnairee. Thosewho were aware of being diagnosed with AR or had two/more AR defining symptoms in the questionnaireÂ form were considered to have AR. The statistical analysis was conducted by calculating frequencies.Results: A total of 207 questionnaire forms were adequately filled out and returned. Based on theÂ questionnaire, the prevalence rate of AR was 38.2%. Of the 79 AR cases, 66% cases involved females. InÂ addition, 54% of the the AR cases have a parental history of allergic diseases. Nasal obstruction and itchyÂ nose were the most frequent symptoms (90%), followed by rhinorrhea (89%), sneezing (82%), and eyeÂ symptoms (62%). Based on the duration, the majority fell into the intermittent group (91%); whereas basedon severity, the majority was in the moderate-severe group (71%).Conclusions: The prevalence rate of AR obtained in this study is within the estimated range of AsianÂ population. [AMJ.2015;2(4):620â5]Â DOI:Â 10.15850/amj.v2n4.658